Keterlekatan Ekonomi Terhadap Kehidupan Sosial - Melis Melis (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2018)
Abstract: Basically, economic factors play an important role in human life. Economics does cover many fields in people's lives, especially in the socio-cultural field. Economic factors in social life play an important role in determining the level of social status of a person or group of people in their environment. In social life there are several factors that influence the level of a person's social status, namely economic factors, educational factors, hereditary factors, and a person's job factor. But in social life in Indonesia, generally economic factors are the main things that can be used as a benchmark for a person's social status. A person with a high level of wealth will be different in lifestyle and habits compared to people who are below the standard level. This social stratification certainly causes some of the impacts that occur in social life, both negative and positive impacts. Keywords: Economy, Education, Social Abstrak: Pada dasarnya, faktor ekonomi memegang peranan penting dalam kehidupan manusia. Ekonomi memang mencakup banyak bidang dalam kehidupan masyarakat, terutama bidang sosial budaya. Faktor Ekonomi dalam kehidupan bermasyarakat memegang peran penting dalam menentukan tingkat status sosial seseorang atau sekelompok orang di dalam lingkungannya. Dalam kehidupan bermasyarakat ada beberapa faktor yang mempengaruhi tingkat status sosial seseorang, yaitu faktor ekonomi, faktor pendidikan, faktor keturunan, dan pekerjaan seseorang. Tetapi dalam kehidupan bermasyarakat di Indonesia umumnya faktor ekonomi adalah hal utama yang dapat dijadikan sebagai tolok ukur status sosial seseorang. Seseorang dengan tingkat kekayaan yang tergolong tinggi akan berbeda pola hidup dan kebiasaannya dibandingkan dengan orang yang tingkat ekonomi di bawah standar. Stratifikasi sosial ini tentunya menimbulkan beberapa dampak yang terjadi dalam kehidupan sosial, baik dampak negatif maupun dampak positif. Kata Kunci: Ekonomi, Pendidikan, Sosial DOI: 10.15408/sjsbs.v5i1.7908